Implementasi Analisis Tingkat Kepuasan Belajar melalui Design Thinking (Studi pada Mahasiswa Program MOOC 2025 di Universitas Bina Darma) - Chaterine Imelga Destriyanti; Rizki Amaliah (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
The development of digital technology has brought significant changes to the world of education, particularly through the use of open and flexible online learning. One rapidly growing innovation is the Massive Open Online Course (MOOC), a digital-based learning model that allows the wider community to access quality education without space and time limitations. The method used in this Community Service is a qualitative method with data collection techniques using questionnaires, interviews, and documentation. The results of this Community Service show that student learning satisfaction in the 2025 UGM MOOC activity is formed through the relationship between students' subjective perceptions and objective learning achievements. In general, students are satisfied with the flexibility of learning, ease of access to materials, and the benefits of learning that support independence and broadening of knowledge.